SOCIALIZATION OF PREVENTION OF JUVENILE DELINQUENCY FOR THE REALIZATION OF A QUALITY YOUNG GENERATION - Titi Rohaeti; Muchammad Sape; Cica Ratna Ningsih; Dewi Anggita; Ella Nur Amelia (Ann Publisher, 2024)
The implementation of Community Service activities, especially in the SMP Negeri 2 Sumber school, is a form of our concern for students so that they avoid juvenile delinquency. According to Amdadi et al. (2021), adolescence is a transition period from childhood to adulthood, and during this period, there have been various physiological, social, and emotional changes. They want freedom so that they can cause conflicts within themselves, so they need a way to understand the essence and way of thinking of teenagers. We hope that this socialization can be a provision for students in facing their adolescence because, in this activity, we give them an overview of what they will face when they step on teenagers, the types of juvenile delinquency, the impact of juvenile delinquency, and solutions when facing a problem. This service involved field supervisors, pamong teachers, and PPL students. We carry out pretest (before) and posttest (after) this service to ensure our research's scientific rigor and validity. The results of the pretest and posttest that we conducted showed an increase in students' understanding of the impact of juvenile delinquency so they were more vigilant in socializing.